Comparing Thyroid Biomarkers And The Quality Of Nuclear Scan Images Of Patients With Thyroid Cancer After Levothyroxine Withdrawal Or Receiving Thyrotropin Alfa: A Retrospective Study (Journal of Pharmaceutical Negative Results, 2022)
Background: Thyroid scan is a specialized imaging method for assessing thyroid cancer after thyroid gland removed. To prepare the patient before scanning the thyroid gland, levothyroxine withdrawal or injection of thyrotropin is done. The aim of the study: The present study aimed to evaluate the quality of nuclear scan images and thyroid biomarkers after levothyroxine withdrawal or receiving thyrotropin alfa. Materials and Methodology: This was a cross-sectional study. The statistical data of this research were composed of 80 female patients with thyroid cancer referred to the nuclear medicine department of the Namazi Hospital in Shiraz in 2019. To be eligible to participate in this study, the patients must have a history of thyroidectomy, a Body mass index (BMI) of between 26 and 30 kg/m2, and no history of receiving radioactive iodine uptake. To nucleus scan of the thyroid gland, all patients received 150 millicuries of radioactive iodine. Patients were divided into two groups. The first group consisted of 40 patients who had discontinued levothyroxine a few weeks before the nuclear scan. The group consisted of 40 patients who continued levothyroxine and received thyrotropin alfa (Thyrogen brand name) before the nuclear scan. These two groups were compared in terms of the levels of thyroid-stimulating hormone (TSH), Triiodothyronine (T3), thyroxine (T4), and thyroglobulin (Tg) biomarkers and image quality following the opinion of nuclear medicine experts and the Region of Interest (ROI) criterion. The results: There was no statistically significant difference between the two groups in T3 and T4 levels. In contrast, the mean TSH level was 67.37±13.98 mIU/L in patients with thyroid hormone withdrawal (THW) and 72.90±16.50 mIU/L in patients who had received thyrotropin alfa injections (P<0.001). The mean Tg levels in the THW and thyrotropin alfa injection were 244.58±88.48 mIU/L and 198.40±61.76 mIU/L, respectively (P<0.001). The means of the body count parameter in the THW and thyrotropin alfa injection groups were 37629.28±9817.08 m2 and 21165.25±3346.64 m2 (P <0.001), respectively. Based on the comments of nuclear medicine physicians, the high qualities of the images were 27.5% and 65% in patients with THW and who had been injected with thyrotropin alfa, respectively. Discussion and Conclusion: The TSH biomarker was higher in patients who had gotten thyrotropin alfa injections, which prepared these patients for the thyroid nucleus scan without the patient's developing symptoms of hypothyroidism. Tg levels were higher in patients with THW, suggesting the likelihood of recurrence of disease, metastasis, and/or residual thyroid tissue in this group. The body count parameter was higher in patients with THW, indicating lower image quality in this group than in the group receiving thyrotropin alfa injections. Besides, the image quality was better in the thyrotropin alfa injections group. Therefore, according to the results of this study, receiving thyrotropin alfa injections was preferable to discontinuation of levothyroxine.